A one-pot diastereoselective self assembly of C-stereogenic copper(I) diphosphine clusters - Yang, Xiang-Yuan (2014)
C-chirogenic diphosphine-based clusters with 8-membered “chairlike” Cu4Cl4L2 and 12-membered “drumlike” Cu6Cl6L3 (L = diphosphine) frameworks were prepared in one-pot syntheses from chiral diphosphines, which were generated in situ via the double hydrophosphination reaction in excellent enantio- and diastereoselectivity. Excellent control over the final molecular architecture of the cluster (drum vs chair) could be achieved by the judicious selection of the source of the copper atoms employed in the synthetic protocol. Each cluster was characterized by single-crystal X-ray crystallography, 1H, 13C, and 31P{1H} NMR spectroscopy. The synthesized clusters were found to exhibit catalytic activity in the hydroboration reaction of α,β-unsaturated enones with excellent yields albeit with low enantioselectivity.